Upaya Pemerintah Kepulauan Faroe Melindungi Aboriginal Subsistence Whaling (ASW) dalam Tradisi Grindadrap - Framestica, Citra Citra Devy (2022)
This research explains how the phenomenon of whaling on Grindadrap tradition in the Faroe Islands has been widely protested and criticized at the international stage, as well as what steps have been taken by the Government of Faroe Islands in protecting the activities of Aboriginal Subsistence Whaling (ASW). The conceptual framework used in this research are Indigenous Peoples (IPs) and The Politics of International Law, which include several forms of agreements. The results in this study indicate that in protecting Aboriginal Subsistence Whaling (ASW) on Grindadrap tradition, the Government of Faroe Islands has long had its own domestic policy that regulates all forms of whaling, including Grindadrap. The next step is that the Government of Faroe Islands has ratified the International Covenant on Economic, Social and Cultural Rights (ICESCR), has become the subject of the United Nations Declaration on the Right of Indigenous People (UNDRIP) and the Bonn Convention, as well as collaborated with conservation and marine mammal management such as The North Atlantic Marine Mammals Commission (NAMMCO).